Management of Current Pre Eclampsia - Septiani, Hani; Lestari, Lusi; Ariani, Dini (INDOGENIUS, 2025)
Introduction & Objective: Preeclampsia and eclampsia remain significant health issues contributing to high maternal and perinatal mortality rates, particularly in developing countries. Preeclampsia, characterized by hypertension, edema, and proteinuria during pregnancy, affects 2% to 8% of pregnancies globally and is a major cause of maternal and fetal death. This study aims to review the current management strategies for preeclampsia to prevent its progression into eclampsia and improve maternal and neonatal outcomes. Method: A literature review was conducted using secondary data sources. Articles were obtained through systematic searches in databases such as PubMed and Google Scholar, using keywords like "Management" and "Preeclampsia" from publications between 2020 and 2024 in English and Indonesian. Results: Management of preeclampsia involves several key components: blood pressure control using antihypertensives such as nifedipine and methyldopa; seizure prevention through magnesium sulfate administration; decision-making regarding timing and mode of delivery; careful fluid management to avoid pulmonary edema; nutritional management focusing on sodium restriction and balanced diet; physical activity to lower gestational hypertension risk; and long-term follow-up due to increased cardiovascular risk post-preeclampsia. The literature indicates that a combination of interventions is more effective than single therapy approaches. Conclusion: Comprehensive management of preeclampsia is essential to prevent disease progression and ensure favorable outcomes for both mother and child. Integrated short- and long-term strategies are necessary to improve maternal safety and long-term health quality.